Isotropic three‐dimensional T2 mapping of knee cartilage: Development and validation. Issue 2 (10th May 2017) - Colotti, Roberto; Omoumi, Patrick; Bonanno, Gabriele; Ledoux, Jean‐Baptiste; van Heeswijk, Ruud B.
Abstract : Purpose: 1) To implement a higher‐resolution isotropic 3D T 2 mapping technique that uses sequential T 2 ‐prepared segmented gradient‐recalled echo (Iso3DGRE) images for knee cartilage evaluation, and 2) to validate it both in vitro and in vivo in healthy volunteers and patients with knee osteoarthritis. Materials and Methods: The Iso3DGRE sequence with an isotropic 0.6 mm spatial resolution was developed on a clinical 3T MR scanner. Numerical simulations were performed to optimize the pulse sequence parameters. A phantom study was performed to validate the T 2 estimation accuracy. The repeatability of the sequence was assessed in healthy volunteers ( n = 7). T 2 values were compared with those from a clinical standard 2D multislice multiecho (MSME) T 2 mapping sequence in knees of healthy volunteers ( n = 13) and in patients with knee osteoarthritis (OA, n = 5). Results: The numerical simulations resulted in 100 excitations per segment and an optimal radiofrequency (RF) excitation angle of 15°. The phantom study demonstrated a good correlation of the technique with the reference standard (slope 0.9 ± 0.05, intercept 0.2 ± 1.7 msec, R 2 ≥ 0.99). Repeated measurements of cartilage T 2 values in healthy volunteers showed a coefficient of variation of 5.6%. Both Iso3DGRE and MSME techniques found significantly higher cartilage T 2 values ( P < 0.03) in OA patients. Iso3DGRE precision was equal to that of the MSME T 2 mapping in healthy volunteers, and significantly higher in OA ( P = 0.01). Conclusion: This study successfully demonstrated that high‐resolution isotropic 3D T 2 mapping for knee cartilage characterization is feasible, accurate, repeatable, and precise. The technique allows for multiplanar reformatting and thus T 2 quantification in any plane of interest. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:362–371.